CO2 Storage Site Characterisation using Combined Regional and Detailed Seismic Data: Harvey, Western Australia. (July 2017) - Ziramov, S.; Urosevic, M.; Glubokovskikh, S.; Pevzner, R.; Tertyshnikov, K.; Kepic, A.; Gurevich, B.
Abstract: Some 115 km 2 of regional 3D seismic data were acquired in the first quarter of 2014 near Harvey, Western Australia, for the needs of the South West CO2 Hub project. The survey proved to be of great importance for a regional characterisation of the reservoir, identification of the large structures and key geological interfaces. However, small to medium size structures of interest for the development of the static and dynamic models were poorly imaged in this survey as the recording geometry was adjusted for the greater depths, which was between 2 km and 3 km. To improve the imaging of the shallow structures, a high-resolution (nested) 3D survey centered at Harvey 4 well was undertaken in 2015 (Urosevic et al., 2015). This survey utilised a single geophone and single, 24 s long, broadband (6–150 Hz) sweep combined with high data density to improve signal to noise ratio that was initially lowered by not employing high-power sources and geophone arrays. The results of this high-resolution 3D survey demonstrate that high-density surveys are important even at the characterisation stage and are crucial for development of a detailed static model. For that purpose, both post and pre-stack inversions of these data were utilised to model distribution of paleosols, lenses of high clay content, which are assumed to serve as baffles for CO2 upward migration. A good correlation was established between very low impedance values and increased percentage of paleosols and on the other end of the scale very high impedance values and low porosity sandstones. A pre-stack migrated high-resolution cube and the attribute derived from it, such as coherency and impedance, enabled improved structural and stratigraphic analysis around Harvey 4 well. The results shown were of a crucial importance for the containment studies, development of the dynamic model and establishment of the injection intervals.